The Effect Of Land Fragmentation On Agricultural Sector Regeneration In East Lombok - Muhammad Joni Iskandar; Muhammad Anwar; Handri Jurya Parmi (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose : The purpose of this study is to determine the influence of land fragmentation on the regeneration of the agricultural sector in East Lombok. The location of the study was determined purposively in Keruak and Sakra Districts with a sample of 50 respondents determined by accidental sampling with the criteria of a sample age less than 40 years. Methodology : Analysis of the effect of land fragmentation on the regeneration of the agricultural sector using the Likert scale on all variables. Results : The results of the study show that more than 50 percent of the young generation stated that fragmentation is the cause of narrow land area, decreased production and productivity, low profits, and difficult production diversification. However, more than 90 percent of farmers are ready and will continue family farming activities. Findings: More than 50 percent of farmers stated that the bargaining position of agricultural products has always been low due to fragmentation. Novelty: This research provides new insights into the effect of land fragmentation on the regeneration of the agricultural sector. Originality: This study offers an analysis of the effect of land fragmentation on the regeneration of the agricultural sector using a Likert scale on all variables. Conclusion: Family, extension workers, and community support are needed to build a modern agricultural sector based on the younger generation. Type of paper : Empirical Research Article